Influence of pH on the efficacy of pilocarpine. Issue 5 (May 1978) - David, R; Goldberg, L; Luntz, M H
Abstract : Pilocarpine 4% solutions at pH 4.1 and 5.8 were compared in a double-blind clinical trial on 24 eyes of patients with primary open-angle glaucoma. Each drug was used over a period of 1 week. No significant difference in the lowering of intraocular pressure was found, and the near-neutral solution of pilocarpine was found to be equally stable when compared to the acid solution over a 6-month period.